The importance of nutritional management and education in the treatment of autism - Anna Mandecka; Bożena Regulska-Ilow (National Institute of Public Health - National Institute of Hygiene, 2022)
Autism spectrum disorders (ASDs) are an early-onset neurodevelopmental disorders. The key symptoms of ASD include social deficits, verbal and non-verbal communication deficits, and restricted, repetitive patterns of behaviour, interests, or activities. Dietary patterns have been evidenced to be related to maternal nutritional status that might lead to different metabolic conditions, and maternal metabolic dysfunction has been observed to be associated with ASD. Furthermore growing evidence suggests that the gut microbiota has a role in the pathophysiology of ASD. Differences in composition of the gastrointestinal (GI) microbiota in children with ASD compared to unaffected siblings and/or healthy unrelated controls have been reported in various studies. The above-mentioned ASD factors and symptoms can be regulated by proper nutrition. The importance of nutrition and its possible impact on ASD patients is key to integral therapy. According to numerous research studies, various nutritional approaches succeeded in reducing the severity of patients' core ASD symptoms. The numerous options for diet that is used in the ASD therapy, as described in the scientific literature, are related to the problem of choosing an appropriate nutritional treatment. Each nutrition programme needs to be personalised and tailored to an individual patient. The aim of the paper is to review the available literature on dietary interventions in children with ASD and provide up-to-date evidence.